2010
DOI: 10.1158/1078-0432.ccr-09-2581
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Pharmacodynamic Modeling of an Anti–Interleukin-6 Chimeric Monoclonal Antibody (Siltuximab) in Patients with Metastatic Renal Cell Carcinoma

Abstract: Purpose: Interleukin-6 (IL-6) induces tumor growth, invasion, metastasis, and angiogenesis. Siltuximab (CNTO 328) is a chimeric, murine-human monoclonal antibody that specifically binds human IL-6 with high affinity. C-reactive protein (CRP) can be a pharmacodynamic (PD) marker of IL-6 bioactivity. Reductions in CRP may correlate with clinical activity and IL-6 bioactivity.Experimental Design: Starting-dose selection for this study was based on a previous siltuximab study in multiple myeloma patients. Pharmaco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
97
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 21 publications
10
97
0
Order By: Relevance
“…The mean clearance was similar and ranged from 2.97 to 4.05 mL/d/kg across the 5.5 to 15 mg/kg dose groups. On the basis of a cross-study comparison, the pharmacokinetic profile of CHO-derived siltuximab in patients with cancer appears to be similar to the pharmacokinetic profile of Sp2/0-derived siltuximab (21,22).…”
Section: Pharmacokineticsmentioning
confidence: 92%
See 1 more Smart Citation
“…The mean clearance was similar and ranged from 2.97 to 4.05 mL/d/kg across the 5.5 to 15 mg/kg dose groups. On the basis of a cross-study comparison, the pharmacokinetic profile of CHO-derived siltuximab in patients with cancer appears to be similar to the pharmacokinetic profile of Sp2/0-derived siltuximab (21,22).…”
Section: Pharmacokineticsmentioning
confidence: 92%
“…19). IL-6 is also the primary factor that drives C-reactive protein (CRP) expression (20), and an earlier pharmacokinetic/pharmacodynamic modeling study indicated that CRP was a suitable biomarker of IL-6 bioactivity (21). Suppression of CRP following siltuximab treatment was also seen in previous clinical studies, reflecting neutralization of in vivo IL-6 bioactivity (21,22).…”
Section: Introductionmentioning
confidence: 90%
“…73 However, contrarily to VEGF-targeting antibodies, siltuximab not only inhibits tumor growth by blocking the tumor-stroma interaction but also by interfering with tumor cell-autonomous signaling pathways, and notably with an MCL-1-mediated IL-6-driven antiapoptotic autocrine loop. 74,75 Results from the first phase I clinical trial based on siltuximab were published as early as in 1998, 73 yet more advanced studies lagged for another decade, with results from phase II studies being reported in the early 2010s, [76][77][78][79] along with an ever more refined pre-clinical characterization of this mAb. [80][81][82][83][84] Siltuximab is currently being tested in a phase III study in combination with the proteasomal inhibitor bortezomib and dexamethasone (a synthetic glucocorticoid) for the treatment of subjects with relapsed or refractory multiple myeloma (Table 3, NCT01266811).…”
Section: Monoclonal Antibodies Under Advanced (Phase Iii-iv) Clinicalmentioning
confidence: 99%
“…Some preliminary results from the completed trials indicate minimal side effects with the inhibitor; however, there was a general lack of correlation with IL-6 inhibition and reduction in tumor growth. 125,126 The lack of tumor inhibition may be due to the nature of the trial that attempted to ascertain the safety profile of the drug, thereby leading to the use of a lower dose than may be effective. 128 In addition, siltuximab has been shown in mice to inhibit the conversion of androgen-dependent prostate cancer into a more aggressive, bone metastatic, and difficult to treat androgen-independent prostate cancer.…”
Section: Il-6 As a Target For Therapymentioning
confidence: 99%